Salama’s Hallucinations Analysis in Zoulfa Katouh’s As Long As The Lemon Trees Grow - Aulia Hapsari Fadhilah; Sri Sumaryani (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
War is a violent event that can lead to psychological destruction, such as depression, deep trauma, and others. Depression and trauma can cause hallucinations. Hallucinations are psychological disorders when someone sees or hears something that actually does not exist. The unconscious mind, painful memories, and deep trauma can profoundly influence hallucinations, much like a dream does. This article aims to reveal and show the representations of unconscious desire, fear, and trauma through the hallucinations that are experienced by the main character in Zoulfa Katouh’s As Long As The Lemon Trees Grow. The method used is qualitative and is analyzed using Sigmund Freud’s theory of the unconscious mind. The results of this research show that Salama's hallucinations have a close relationship with the unconscious mind. The hallucinating figure of Khawf represents Salama's deep fear and trauma, as Khawf constantly reminds her of the stern warning that compelled Salama to flee the conflict occurring in her country. Meanwhile, the hallucinating figure of Layla is a representation of her hidden desires, a sense of security and companionship in a world that has become unbearable.